BELIEFS ABOUT TRANSLATOR COMPETENCE AND TRAINING PRACTICES: TEACHERS’ AND STUDENTS’ PERSPECTIVES - Sonja Kitanovska-Kimovska, Milena Sazdovska Pigulovska, Solzica Popovska (University of Niš, Serbia, 2025)
There has been some research at the intersection of beliefs and translation (as a form of applied language knowledge) in recent times. Investigations have focused on translators’, students’ and teachers’ beliefs about different aspects of translation, including translation as a product, a process or a subject of teaching and learning. The topics of interest have ranged from translators’ beliefs about the professional world of translators (Katan 2009), the impact of translators’ beliefs on translation quality (Araghizade 2016, Yousefi 2017), teachers’ and students’ beliefs on the nature of knowledge and learning (Li 2017), teachers’ practices and beliefs about inclusion in the English language classroom (Al Siyabi et al. 2024), teachers’ and students’ beliefs about translator competence and training practices (Wu et al. 2019), to teachers’ beliefs on the role of machine translation in translator education (Hellmich and Vinall 2021, Rico and Pastor 2022). This paper aims to add to this body of knowledge by exploring teachers’ and students' beliefs about translator competence and training practices in the Macedonian context. The purpose of this paper is to identify and compare the beliefs held by translation students and their teachers with reference to translator competencies as well as to explore the way in which these are addressed in existing training practices. The study presented in this paper is conducted among students and teachers at the Department of Translation and Interpreting at the “Blaze Koneski” Faculty of Philology in Skopje, Republic of North Macedonia, using a mixed method approach following Wu et al. (2019). The paper addresses three research questions: what teachers and students believe are the components of translation competence, how much they think these are addressed in current training practices and the similarities and differences between the beliefs of both groups. The results of the study have pedagogical implications. They help teachers become aware of their own beliefs about the importance of the different subcomponents of translation competence and whether these are reflected in their teaching practice. The results also help increase teachers’ awareness of the translation students’ beliefs about translation competence as well as their perception of the teaching methods. Finally, the results show if there are any mismatches between the beliefs of the two groups that need to be addressed in future practice and research.
Keywords: teachers’ and students' beliefs, translator competence, training practices